Fundamentals of diagnostic cytology in preclinical cervical neoplasia - Dabances Opazo, Alfredo (2015)
The various tissues that make up the human body have been classified by Bizzozero perennial, stable and labile, according to the life cycle of cells they contain. Perennial tissues are composed of highly differentiated cells that appear during embryonic and fetal growth and physiological conditions that do not multiply or die throughout postnatal life of the individual. Neurons of the central nervous system are representative of such tissue have also been called static cell populations, because the total amount of DNA • containing, remains constant throughout life.